BONDING PREFERENCES OF NON-BRIDGING O ATOMS: EVIDENCE FROM 17O MAS AND 3QMAS NMR ON CALCIUM ALUMINATE AND LOW-SILICA CA-ALUMINOSILICATE GLASSES - Allwardt J.R.; Lee S.K.; Stebbins J.F. (My University, 2003)
The fraction of O atoms as non-bridging O atoms (NBO) can be well approximated based on composition alone in many silicate glasses, but the NBO preference for specific network forming cations is much less well known. Using oxygen-17 (17O) NMR on low-silica calcium aluminosili-cate (CAS) glasses, this study shows that Al-NBO (155 ppm) can be readily distinguished from Si-NBO (110-120 ppm), and that there is a strong preference for the latter. This study also pre-sents a consistent equilibrium constant formulation that indicates that for thermodynamic model-ing of most CAS melts with Si > Al, Al-NBO are of minor importance, although they could be significant in some models of diffusion and viscosity. Al-27 one pulse NMR and analyses of spinning side bands show that AlO5 and AlO6 species are below detection limits (<0.5%) in the low-silica (SiO2 ≤ 20 mol%) glasses of this study (NBO/T = 0.6 to 0.8). In addition, 17 O MAS NMR does not detect any obvious (<2%?) Al3O triclusters; hence calculations of NBO assign-ments can be assigned unambiguously.
Keywords: ATOMS & SUBATOMIC PARTICLES; CALCIUM; MINERALOGY; GLASS & GLASSWARE INDUSTRY